Innovation Management and Trends in Management Sciences: a modular approach - Tostes, Marta (2024)
In this number 9 of 360 Journal of Management Sciences, we organize the articles into four large blocks, with the first three associated with: five documents on strategic management of CTI; another five related to tools for technology and innovation management; and two focus on innovative university. Furthermore, due to the urgency of the topic to be discussed, we have selected the publication of two articles linked to the field of trends in labor relations such as remote work and the sectoral centralization of collective agreements for the final module. With these 14 articles, 360 Revista de Ciencias de la Gestión seeks to continue contributing to the production of knowledge in our discipline and link it with its thematic environment, reviewing the trends from the academy, but with a very focused view on what is happening in the reality of organizations at the national and international level. In times of such relevant changes in the way of understanding the conditions for the creation of value in the business environment, we must analyze the elements that promote its sustainability and the promotion of innovations in different organizational ecosystems.